A rare case of huge retrosternal goiter - Bansod, Atish; Gandhi, Khushbu; Umalkar, Rohan; Mishra, Sarvagya; Tayde, Priyanka; Awachar, Neha (International Surgery Journal, 2019)
Retrosternal goiter is defined when more than or equal to 50% of the thyroid mass is below the thoracic inlet. A median sternotomy approach is required in selected cases especially those presenting with long standing history and radiological assessment is suggestive of thoracic component larger than thoracic inlet. The case reported by us was a 65 year old lady with huge retrosternal goiter with history of dyspnea. Her contrast-enhanced computed tomography neck and thorax suggested diffuse enlargement of both lobes with mediastinal extension and pressure effects in the form of luminal narrowing of trachea. A total thyroidectomy was performed with median sternotomy. No post-operative complications occurred and patient was discharged on 6th post-operative day. Histopathology suggested multinodular goiter.